Off center the Republican revolution and the erosion of American democracy - Hacker, Jacob S.; Pierson, Paul 1959- (Yale Univ. Press, 2005)
The Republicans who run American government today have defied the normal laws of political gravity. They have ruled with the slimmest of majorities and yet have transformed the nation's governing priorities. They have strayed dramatically from the moderate middle of public opinion and yet have faced little public backlash. Again and again, they have sided with the affluent and ideologically extreme while paying little heed to the broad majority of Americans. And they have come out on top. This book shows why--and why this state of affairs can and must be changed. Written by two professional political scientists, it tells the story of a deliberative process restricted and distorted by party chieftains, of unresponsive power brokers subverting the popular will, and of legislation written by and for powerful interests and deliberately designed to mute popular discontent.--From publisher description.
Includes bibliographical references and index
Keywords: Republican Party (États-Unis : 1854- ); Republican Party (U.S. : 1854- ); Republican Party -- USA; Geschichte; Conservatisme - États-Unis; Conservatism -- United States; Konservativismus; USA